Nabis: un prince hellénistique ? - Birgalias, Nikos (Gerión. Revista de Historia Antigua, 2006)
The purpose of this study is to explore the extent to which Nabis can be included among the Hellenistic rulers, the principles upon which his political model was based and how we can interpret his policies. With this purpose in mind, the political situation that prevailed in Sparta prior to Nabis’s rule, his assumption of power, his political and social reforms and his foreign policy are explored. Nabis is approached as the type of figure who, exploiting social disorder, establishes a regime of personalised power that enjoys popular support, thus enabling him to institute a new order of things. This study concludes that, as regards the changes that he brought about to Sparta’s social and political structures, Nabis appears as a “traditional” reformer within the context of the city-state. On the contrary, as for the political system that he applied and the foreign policy that he exercised, he comes across as a Hellenistic ruler. Nabis, in other words, attempted to combine reform on the level of the polis with the model of the supra-polis king of the Hellenistic era.